A multicenter study on the appropriateness of hospitalization in obstetric wards: application of Obstetric Appropriateness Evaluation Protocol (Obstetric AEP). (29th September 2014) - Mannocci, Alice; Specchia, Maria Lucia; Poppa, Giuseppina; Boccia, Giovanni; Cavallo, Pierpaolo; De Caro, Francesco; Vetrano, Giuseppe; Aleandri, Vincenzo; Capunzo, Mario; Ricciardi, Walter; Boccia, Antonio; Firenze, Alberto; et al.
Abstract: The cross-sectional study has been based on the implementation of the Obstetric Appropriateness Evaluation Protocol (OAEP) in seven hospitals to determine inappropriate hospital admissions and days of stay. The outcomes were: inappropriateness of admission and "percentage of inappropriateness" for one hospitalization. A total number of 2196 clinical records were reviewed. The mean percentage of inappropriateness for hospitalization was 22%. The percentage of inappropriateness for the first 10 d of hospitalization peaked in correspondence of the fourth (42%). The logistic regression model on inappropriated admission reported that emergency admission was a protective factor (OR = 0.4) and to be hospitalized in wards with ≥30 beds risk factor (OR = 5.12). The second linear model on "percentage of inappropriateness" showed that inappropriated admission and wards with ≥30 beds increased the percentage ( p < 0.001); whereas the admission in Teaching Hospitals was inversely associated ( p < 0.001). The present study suggests that the percentage of inappropriate admission depends especially on the inappropriate admission and the large number of beds in obstetric wards. This probably indicates that management of big hospitals, which is very complex, needs improving the processes of support and coordination of health professionals. The OAEP tool seems to be an useful instrument for the decision-makers to monitor and manage the obstetric wards.